The relationship between Hb examination and body height on the incidence of stunting in elementary schools - Butarbutar, Maria Haryanti; Bangun, Herianto; Zebua, Arianus; Siregar, Riani Baiduri (Institute of Computer Science (IOCS), 2024)
Stunting is known as a child's short or very short height. Stunting is a nutritional problem that can affect the quality of human resources. As a result, stunting includes increased mortality and morbidity as well as decreased growth in motor and mental abilities. Based on the monitoring results of the North Sumatra Provincial Government, the prevalence of stunting will be 18.9% in 2023. One of the global health problems, especially in developing countries, is anemia. The purpose of the study was to understand the relationship of Hb examination and anemia to the incidence of stunting in elementary schools in Medan. The method used in this study was quantitative method, namely survey with cross-sectional technique, the respondents were all public elementary school students. Sampling by cluster, namely class 1 as many as 28 samples. The results of Hb examination with the incidence of stunting p-value 0.061 which means less than 0.05 there is a relationship between Hb examination and the incidence of stunting. The results of height with the incidence of stunting p-value 2.652 which means greater than 0.05 that there is no relationship between less height and the incidence of stunting. Normal height with the incidence of stunting p-value 2.652. The type of food consumed by the body affects the absorption of iron in the body, especially non-heme iron of vegetable origin. Consumption of high doses of calcium (more than 40 mg) may inhibit iron absorption and lead to low haemoblogin and short stature in children.